Instructional guides for filming infant movements at home are effective for the General Movements Assessment. (30th November 2021) - Kwong, Amanda K L; Eeles, Abbey L; Olsen, Joy E; Zannino, Diana; Kariotis, Timothy; Spittle, Alicia J
Abstract : Aim: To determine the effectiveness of two instructional guides to obtain video recordings for the General Movements Assessment (GMA). Methods: A cross‐sectional study of a community sample of family participants with low‐risk term newborn infants recruited via social media and randomly allocated to receive one of two instructional guides (detailed or quick versions) to film their infant's movements at home. Participants returned videos via a secure Research Electronic Database Capture link and videos were scored for quality across 10 criteria, along with scoring the GMA. Participants were surveyed about their perceptions of the instructional guides and electronic file transmission. Results: Seventy‐six parents of infants were enrolled and randomly allocated to receive detailed ( n = 38) and quick ( n = 38) instructions to film their infant for a GMA. Videos were returned by 87% (95% confidence interval (CI) 72%, 96%) of detailed instruction users and 84% (95% CI 69%, 94%) of quick instruction users. The GMA could be conducted on all returned videos. The mean score for video quality was 9.9/10 (standard deviation 0.4, 95% CI 9.7, 10.0) for detailed instructions and 9.7 (standard deviation 0.6, 95% CI 9.4, 9.9) for quick instructions. Overall, participants felt that either instructional guide was easy to use. Fifteen (20%) participants had difficulties with video file transmission, requiring additional support. Conclusions: Parents can successfully use one of two different instructional guides for filming their infant's movements for GMA; however, support should be provided for safe and easy file transmission.